Dermatophytosis Agents in Patients Who Attending to Dermatology Clinic of Firat University Hospital - Dilek, Nursel; Yucel, Ahmet Yasar; Dilek, Aziz Ramazan; Saral, Yunus; Toraman, Zulal Asci (Galenos Yayincilik, 2009)
Objective: We aimed to investigate the types of dermatophytes and dermatophytosis in Elazig region to provide appropriate information for therapy planning and public health prevention. Methods: A total of 652 patients who attending to outpatient clinic between June 2007-May 2008 with clinical signs of dermatophytosis were included in this study. All samples, including with negative results on direct microscopy were cultivated in Sabouraud dextrose agar (Oxoid), mycobiotic agar (Acumedia) and potato dextrose agar (Oxoid). Results: Dermatophytes were isolated in 142 (21.8%) out of all samples. Of the isolates 70.4% were Trichophyton rubrum, 15.4% were Trichophyton mentagrophytes, 4.2% were, 4.2% were Microsporum canis, 2.8% were Epidermophyton floccosum, 2.11% were Trichophyton violaceum, 0.7% were Trichophyton tonsurans. Conclusion: Trichophyton rubrum was most frequently isolated dermatophytosis agent in Elazig region.
Firat Üniversitesi Hastanesi dermatoloji klini?i'ne başvuran hastalardaki dermatofitoz etkenleri
Keywords: Dermatophytes; dermatophytosis